Infertility screening in unmarried women: A scoping review protocol - Sanam Borji-Navan; Nasser Mogharabian (PLoS ONE, 2025)
Objective This scoping review aims to systematically map the landscape of infertility screening in unmarried women. Introduction Infertility screening in unmarried women represents a significant and often neglected area within reproductive health. This population faces unique challenges and barriers, including social stigma, cultural norms, and limited access to care, making a comprehensive understanding of current screening practices essential. Inclusion criteria Study selection will be guided by the PCCT framework (Population, Concept, Context, and study type), considering diverse study designs (quantitative, qualitative, mixed-methods, reviews) and grey literature, focusing on infertility screening in unmarried women. Methods This scoping review will follow the PRISMA-ScR guidelines and utilize a 14-step framework based on Arksey and O’Malley’s methodology, incorporating enhancements by Tricco and Peters. A comprehensive search strategy will be employed, using controlled vocabulary and free-text method. Databases of Web of Science (ISI), PubMed, Scopus and search engines like Google Scholar will be searched, and supplemented by forward and backward citation tracking. Inclusion/exclusion criteria will be applied iteratively. Two independent reviewers will screen titles/abstracts and full texts, resolving disagreements through consensus or a third reviewer. Data will be charted using a predefined template, and findings will be presented in tables and diagrams, accompanied by a narrative synthesis. Discussion This scoping review will provide a comprehensive overview of the current state of knowledge regarding infertility screening in unmarried women, a significantly under-researched area. The findings will be critical for informing the development of culturally sensitive guidelines, targeted interventions, and future research to address the reproductive health needs of this underserved population.